NILAI TAMBAH INDUSTRI PENGOLAHAN KAYU JA TI PERUM PERHUTANI UNIT I JAWATENGAH - Hendro Prahasto; Boen M Purnama (Pusat Penelitian dan Pengembangan Hasil Hutan, 1994)
The export tariff policy on sawntimher is aimed at accelerating the development of high volue-added industry. Study on the valu- added of teak processing industry belongs to the State Forestry Company (Perum Perhutani) is focused on sawntimber. and woodworking products such as doors, windows, frames, decking and parquets.Study result shows that not all sawmill plants provided positive value added. in aggregate, sawntimber industry yields value added of Rps. 55, 542 per cu. m or 11 percent of processed raw material value. Wood working industry yielded a higher value added, Rps.1,023, 791 per cu. m or almost half of its raw material value